Effects of packaging materials and types on the postharvest nutritional quality of mini Pakchoi Brassica chinensis - Shimin, Wu; Feiya, Shu; Danfeng, Huang (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: The baby leaves of mini Pakchoi Brassica chinensis are gaining popularity due to its pleasant appearance, flavour, tender texture and nutrition. Effects of retail packaging on the nutritional quality of Brassica chinensis at 4°C were studied. Samples were packaged using polyethylene bags (PE-B), polystyrene foam tray covered with polyethylene film (PE-C/PS-T), perforated oriented polypropylene bags (POPP-B) and biaxially oriented polystyrene box (BOPS-B). Weight losses, respiration rate, chlorophyll and carotenoid, vitamin C and nitrate were determined during storage period. After 10 d storage, the weight loss for samples packaged in PE-B was 0.89%, followed by PE-C/PS-T with weight losses of 6%. A significant reduction (>10%) in moisture was observed for the samples packaged in POPP-B and BOPS-B. The variation in respiration rate during storage seemed to form a trend with a sharp decline up to the fourth day. The difference in the reduction of chlorophyll and carotenoid was not significant among the four packages. BOPS-B had a better protective effect on vitamin C loss. The nitrate concentration during storage was within the official limit. Keywords: Brassica chinensis, packaging, vitamin C, chlorophyll, carotenoid, nitrate-nitrogen DOI: 10.3965/j.ijabe.20160906.1746 Citation: Wu S M, Shu F Y, Huang D F. Effects of packaging materials and types on the postharvest nutritional quality of mini Pakchoi Brassica chinensis. Int J Agric & Biol Eng, 2016; 9(6): 207-213.